(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
The semiotics of the title is an important issue that has preoccupied critics. The title is the gateway to the text, an integral part of its content, and the primary threshold for understanding the text and entering its world. One cannot begin analyzing a short story without first examining and analyzing the structure of the title, which is the interface that reveals the text’s connotations and plays a semiotic and aesthetic role. This research aims to examine the semiotics of the title in the short story collection (Tales of the Migrant Seagull) by Haidar Haidar. In the theoretical aspect, it reviews the concept of semiotics and its origins. It then moves to the concept of the title, its importance, functions, and types, as a linguistic and cultural sign that defines the identity of the text. Then, in the applied aspect, it addresses the interactive relationship between the title and the cover, to clarify the importance of integration between linguistic and visual elements. After that, it delves into the levels of the title that work to attract the reader to the text and provide him with indications to reveal aspects of the content, focusing on the relationship between the main title and the subtitles, clarifying the semantic links between these titles. Through a semiotic analysis of the title, the author’s vision and the context in which the text was produced can be revealed.